REALIZATION OF THE TEST SYSTEM DEVELOPING AND CONTROLLING FUNCTIONS IN THE VISUAL BASIC PROGRAMMING ENVIRONMENT IN PHILOLOGICAL SPECIALTIES - Сухов, М.В.; Кудрицкая, М.И.; Каппассова, А.Н.; Лифенко, В.М. (My University, 2016)
In the paper a description of the program realized in the Microsoft Visual Basic 6.0 programming language is offered. Its application for philological spe-cialties students’ knowledge assessment is given. Controlling and developing possibilities of tests of the closed type are considered.
Keywords: testing system; the language of a programming controlling functions